Challenging the limits in pancreatic surgery: A case report. (2016) - Lemke, Johannes; Schmidt, Stefan A.; Kornmann, Marko; Orend, Karl-Heinz; Henne-Bruns, Doris
Highlights: Despite the great progress remains challenging in many cases due to proximity of main vascular structures. This unique cases demonstrates the complex surgical procedure of a partial pancreaticoduodenectomy in combination with a mesenterico-caval shunt. Autoimmune pancreatitis is a relevant differential diagnosis of pancreatic conditions which may require complex surgical approaches. Abstract: Introduction: Today, pancreatic surgery can be performed with low mortality and tolerable morbidity in specialized centers. Nevertheless, due to its anatomical localization and proximity to important vascular structures, surgical resection of the pancreas remains challenging in many cases. Presentation of case: Here, we present the case of a young woman who presented in our department with abdominal pain and a tumor mass located at the pancreatic head. She had undergone explorative laparotomy elsewhere before, in which the pancreatic tumor mass was reported to be unresectable due to infiltration of the mesenteric root. However, biopsies obtained had not revealed malignancy. Moreover, postoperatively a stenting of the portal vein had been performed due to portal vein thrombosis and varices. Upon admission in our clinic, computed tomography revealed a tumor of the pancreatic head, occlusion of the portal vein stent and, more importantly, extravascular dislocation of the stent with perforation into the stomach. Upon explorative laparotomy we initially performed a mesenterico-caval shunt to release portal hypertension. Secondly, the dislocated stent was successfully removed upon gastrotomy, and finally, a partial pancreaticoduodencectomy was performed. Interestingly, the histopathological analysis revealed granulocytic epithelial lesions (GELs) confirming a type-2 autoimmune pancreatitis without evidence for malignancy. The postoperative course was uneventful and the patients was dismissed without any remaining symptoms. Discussion & conclusion: This interesting and unique case underlines the complexity in diagnosis of pancreatic tumors with unsolved dignity and differential diagnosis of pancreatitis and pancreatic cancer. Furthermore, it demonstrated the challenges in pancreatic surgery for exceptional and uncommon conditions demanding complex surgical approaches.